Néologismes en discours spécialisé. Analyse comparée des noms de stades de football dans quatre pays europeens - Bach, Matthieu; Fernández-Cruz, Javier; Gautier, Laurent; Koch, Florian; Llorca, Matthieu (Estudios románicos, 2022)
The present contribution intends to innovate in neology and onomastic analysis, by relying on an empirical study of soccer stadium names in France, Germany, England and Spain, in order to validate on corpus a holistic, discursive, cognitive, and interdisciplinary approach of neology. For this purpose, we will establish a theoretical framework, based on the recognition of the limits of formal models of neology, in order to integrate discursive variables, and also to capture the totality of the social mechanisms governing the displayed use of linguistic structures. These structures are characterized by non-compositionality and specialized informational linearization. In fact, the soccer stadium names, result of the naming process, related to the commodification of the soccer sector, deploy a new neologic structure such as <[SPONSOR]+ [GENERIC TOPONYM]>, which gives birth to results such as Allianz Arena or Emirates Stadium. This analysis of stadium names is part of a larger project focused on specialized discourses. La présente contribution entend innover dans l’analyse néologique et onomastique, en partant d’une étude empirique de noms de stades de football en France, Allemagne, Angleterre et Espagne, pour valider sur corpus une approche holistique, discursive, cognitive et interdisciplinaire de la néologie. En effet, à cette fin, nous déployons un cadre théorique reposant sur la reconnaissance des limites des modèles formels de néologie, afin d’intégrer les variables discursives, dans le but saisir la totalité des mécanismes sociaux régissant l’usage attesté de structures linguistiques. Lesdites structures se caractérisent par une non-compositionnalité et une linéarisation informationnelle spécialisée. En effet, les noms de stade, issus du processus de naming, relatif à la commodification du secteur du football, déploient un schéma néologique nouveau tel que <[SPONSOR]+[TOPONYME GENERIQUE]>, permettant de générer des réalisations, tels que Allianz Arena ou Emirates Stadium. Cette analyse des noms de stade s’insère dans un projet plus vaste d’étude des discours de spécialité. ras